2017
DOI: 10.22159/ijpps.2017v9i6.17464
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacist-Led New Medicine Service for Patients With a Long Term Medical Condition: A Cross-Sectional Study

Abstract: Objective: This study assessed the impact of the new medicine service (NMS) on medication use in patients starting a new medication for a longterm medical condition in the United Kingdom (UK). Methods:A cross-sectional study was conducted in community pharmacies in the West Midlands area for three months from July to September 2012. The drug therapies/agents included in the study were antihypertensive, antidiabetics, anti-asthmatics and antiplatelet/anticoagulants.Results: 20 community pharmacists completed qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Very little information is available in the literature on the extent of discussion or advice on health behaviours during consultations. A pharmacist completed survey reported over a fifth of NMS patients received advice on such issues, most commonly on diet, with alcohol and smoking advice provided to around 40% of these patients 60 . Such shortcomings extend beyond the conduct of MURs and the NMS, indicating broader challenges to moving from a traditional community pharmacist role to consistent adoption of patient-centred approaches to practice.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Very little information is available in the literature on the extent of discussion or advice on health behaviours during consultations. A pharmacist completed survey reported over a fifth of NMS patients received advice on such issues, most commonly on diet, with alcohol and smoking advice provided to around 40% of these patients 60 . Such shortcomings extend beyond the conduct of MURs and the NMS, indicating broader challenges to moving from a traditional community pharmacist role to consistent adoption of patient-centred approaches to practice.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, interventions made by clinical pharmacists are successful in identifying and rectifying the different types of drug-related problems in patients with multiple drug use [43]. Community pharmacists may also contribute to the detection of adverse effects attributed to new medications uses and identify incorrect use of medicines [44].…”
Section: Matalqah Et Almentioning
confidence: 99%
“…The study findings have demonstrated that the community pharmacists possess a positive attitude toward ADR reporting, although the majority of them never reported any ADRs. In a study conducted by Cheema et al in London observed in their study "Community Pharmacist-Led New Medicines Service for patients with long-term medical condition -A cross-sectional study has revealed that ADR reporting has identified new service by community pharmacists to be offered to the patients voluntarily to identify potential ADRs that lead to increased morbidity in patients with chronic diseases not only improves patients health but also the reputation to the pharmacist [13] that similar findings were also observed in the studies conducted at United Arab Emirates and Malaysia with respect to the positive attitude of the community pharmacists in reporting ADRs in the community*pharmacy settings [12,14,15].…”
Section: Srikanth and Adepumentioning
confidence: 99%